A confirmatory factor analysis model of adversity quotient of five year courses’ 3rd year teacher student at Prince of Songkla University, Pattani campus - หนกหลัง, สุเมษย์; ศรีสวนแตง, สันติ; ตันพิชัย, ประสงค์ (Journal of Liberal Arts Prince of Songkla University, 2025)
The purpose of this research was to examine the goodness of fit model between the adversity quotient among students in a teacher education program and empirical data. Data were collected from 411 third year students in the five-year teacher education course at Prince of Songkla University, Pattani Campus in the academic year 2012 using a 1-5 rating scale questionnaire with 25 question items. Thequestionnaire tested by seven experts had item objective congruence (IOC) between .50-1.00, item discrimination (r.) between 0.224- 0.503 and reliability (a). of 0.87. The data were analyzed with second order confirmatory factor analysis. The results were that the adversity quotient among students in a teacher education program consisted of five main factors: 1. control, 2. causes, 3. responsibility, 4. unde rstanding, and 5. patience, and each of these factors consisted of five ind icators which were consistent with the empirical data: = 354.78, df = 257, p-value < .05; Relative = 1.38; GFI = .94; AGFI = .92; RMR = .06; SRMR = .04; RMSEA = .03; P-Value for Test of Close Fit = 1.00; NFI = .94; IFI = .99; CFI = .99; CN = 348.52. The weight of each factor was be tween .49-.75, and the standard weight of each indicator was between .48-.77.